A comparative study on the effect of loading speed and surface scratches on the flexural strength of aluminosilicate glass: Annealed vs. chemically strengthened. Issue 10 (July 2018) - Zhen, Wang; Zhenbiao, Hu; Tao, Suo; Fenghua, Zhou; Yulong, Li; Sheikh, Muhammad Zakir; Xiang, Wang; Yinmao, Wang
Abstract: Quasi-static and dynamic three-point-bending experiments were conducted on both annealed and chemically strengthened aluminosilicate glass scratched by different normal loads. Scratched areas were observed by optical microscope and atomic force microscope. Chemically strengthened glass shows better resistance to surface scratch. These dynamic experiments were carried out using a modified Split Hopkinson Pressure Bar (SHPB) device and a pulse-shaping technique was used to keep constant loading speed to the specimens. In tests, high-speed photography was also used to observe the failure process of the specimens. The test results showed that the flexural strength of aluminosilicate glass (AG) strongly depends on the applied loading speed. Compared with its annealed counterpart, the chemically strengthened glass (CSG) showed higher flexural strength to both static and dynamic loadings. Moreover, the three-point bending experiments were conducted on scratched AG and CSG specimens and decrease of 20–40% in flexural strength was observed. The fractography analysis showed that in dynamic loading conditions the fracture surface was not smooth and has more secondary cracks as compared to static loading.